(3GdfbhO hGdQOhOs - (3eMeO Hf jhSa Hf Ydj Hf SYjO, TeS GdOjf GdcQeGfj , (B786 (3g` s
(3ChdgG (B:s
(3CeG HYO adeG Jhba GSJfHGW GdCMcGe GdTQYjI s
(3BNQgG (B:s
(3hdGjdRe ef LYd GddaX MbjbI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3CUhd Gdabgs